2019
DOI: 10.1038/s41598-018-36941-9
|View full text |Cite
|
Sign up to set email alerts
|

Prominent action of butyrate over β-hydroxybutyrate as histone deacetylase inhibitor, transcriptional modulator and anti-inflammatory molecule

Abstract: Butyrate and R-β-hydroxybutyrate are two related short chain fatty acids naturally found in mammals. Butyrate, produced by enteric butyric bacteria, is present at millimolar concentrations in the gastrointestinal tract and at lower levels in blood; R-β-hydroxybutyrate, the main ketone body, produced by the liver during fasting can reach millimolar concentrations in the circulation. Both molecules have been shown to be histone deacetylase (HDAC) inhibitors, and their administration has been associated to an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
142
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(150 citation statements)
references
References 36 publications
8
142
0
Order By: Relevance
“…However, more recent data from Chriett et al did not confirm the function of BHB as a histone deacetylase inhibitor. Experiments performed on multiple cell lines, including HEK293 cells, myotubes (L6) and endothelial cells (HMEC-1), showed that BHB administration did not increase histone acetylation, and BHB treatment of crude nuclear extracts did not inhibit histone deacetylase catalytic activity [31]. These data are in line with the study performed by Xie et al that presented a BHB dose-dependent induction of β-hydroxybutyrylation on multiple histone lysines with only marginal changes in the acetylation patterns [25].…”
Section: Epigenetic Effects Of Ketone Bodiessupporting
confidence: 87%
“…However, more recent data from Chriett et al did not confirm the function of BHB as a histone deacetylase inhibitor. Experiments performed on multiple cell lines, including HEK293 cells, myotubes (L6) and endothelial cells (HMEC-1), showed that BHB administration did not increase histone acetylation, and BHB treatment of crude nuclear extracts did not inhibit histone deacetylase catalytic activity [31]. These data are in line with the study performed by Xie et al that presented a BHB dose-dependent induction of β-hydroxybutyrylation on multiple histone lysines with only marginal changes in the acetylation patterns [25].…”
Section: Epigenetic Effects Of Ketone Bodiessupporting
confidence: 87%
“…As shown in Figure 2, activation of AcH3K9 is detectable in KERTr cells or mouse skin treated with butyric acid or BA-NH-NH-BA, suggesting that butyric acid or BA-NH-NH-BA may down-regulate the production of IL-6 via the inhibition of HDACs favoring histone acetylation [75]. A modeling study demonstrated that trichostatin A (TSA) exerts its inhibitory effect on HDAC inhibitor by disrupting interactions between the lysine side chain of histone H3 and the acetyl group of HDAC [76].…”
Section: Discussionmentioning
confidence: 90%
“…As observed for the role of SCFAs in depression, butyrate can normalize BDNF expression and depression-like behaviors in animals [200], through mechanisms involving BDNF-5HT synergistic modulation as well as HDAC inhibition and potentiation of 5HT transmission [204]. Not only butyrate administration can promote the recovery of BDNF expression and memory impairment [249], but its activity as HDAC inhibitor provides a mechanistic evidence for the ability to suppress several LPS-induced pro-inflammatory factors [250], which are recognized components of SCZ pathogenesis [251]. Strikingly, stress-induced derangement of gut microbial composition and changes in brain BDNF expression are associated to the alteration of NMDA receptor subunits, such as for the decrease of GluN2A subunit in the hippocampus and cortex of GF mice [32].…”
Section: Scfas Dysbiosis and Neuroinflammation In Asd And Sczmentioning
confidence: 90%